Analysis of heat sources: Alternatives for improving environmental conditions in an underground gold mine (Research, Society and Development, 2023)
Heat generation in underground mines is a factor of extreme influence on the production, safety and comfort of workers. This article aims to analyze heat sources in an underground mine and propose, as one of the alternatives to improve ventilation conditions, replace the diesel fleet with electric. The case study shows that this is the second source of heat, being the first autocompression, the second diesel equipment and the third are the fans. The heat emitted by the rock then stabilizes a certain time having no significance in the temperature in the year of 2019, but in 2026 it will be a significant heat source. This evaluation was carried out in a gold mine near Belo Horizonte, capital of the State of Minas Gerais using the software Ventsim.  In the study, sensitive heat and latent heat would be reduced by about 56% and 80%, respectively, if the change is made. This reduction in the heat generated by the system may improve working conditions because of lower temperature and gas concentration, which reflect on the safety conditions for higher worker's efficiency.